2023
DOI: 10.3390/jcm12072510
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Autism Spectrum Disorders in Greece for 2021: Nationwide Prevalence in 2–17-Year-Old Children and Regional Disparities

Abstract: This study estimated the crude prevalence of autism spectrum disorders (ASD) in Greece in 2021. A retrospective study was conducted for 2021 using data provided for research purposes for the first time by the Greek National Health Service Organization for Healthcare Services Provision (EOPYY) related to the ICD-10 diagnosis codes F84.0–F84.9 (ASD). Treatments were categorized by gender, age, and location. Statistical analysis was performed using the open-source software R. In total, 15,706 children aged 2–17 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It might stem from biological differences between the sexes. A recent study done in our country regarding the prevalence of autism showed that for 2021 8588 males and 2195 females were diagnosed, so the proportion of diagnoses of ASD in relation to sex for the entire age group of 2-17 years was 78•82 % for boys and 21•18 % for girls (70) . In our case, this relationship was a little higher and it is a matter that needs further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…It might stem from biological differences between the sexes. A recent study done in our country regarding the prevalence of autism showed that for 2021 8588 males and 2195 females were diagnosed, so the proportion of diagnoses of ASD in relation to sex for the entire age group of 2-17 years was 78•82 % for boys and 21•18 % for girls (70) . In our case, this relationship was a little higher and it is a matter that needs further investigation.…”
Section: Discussionmentioning
confidence: 90%